Cord blood troponin I levels: biomarker evidence of fetal cardiac injury in intrahepatic cholestasis of pregnancyAJOG Global Reports at a Glance - Itamar D. Futterman, MD; Hitangee Jain; Rodney A. McLaren, Jr; Jonathan K. Mays, MD (AJOG Global Reports, 2024)
BACKGROUND: Intrahepatic cholestasis of pregnancy has been linked to sudden stillbirth. The suddenness of the stillbirths in these cases have led clinicians to suspect that the pathogenesis of stillbirth in women with intrahepatic cholestasis of pregnancy is not related to asphyxia but rather to an undefined etiology. One leading hypothesis relates certain bile acid metabolites to myocardial injury. OBJECTIVE: The purpose of this study was to determine whether cord blood troponin I levels are increased in fetuses born to mothers with a diagnosis of intrahepatic cholestasis of pregnancy. STUDY DESIGN: A prospective, case-control study was performed at a single institution between 2017 to 2019 in which 87 pregnant patients with a diagnosis of intrahepatic cholestasis of pregnancy (total bile acids ≥10 μmol/L) were enrolled as cases and 122 randomly selected pregnant patients (asymptomatic with intrapartum total bile acids <10 μmol/L) were enrolled as controls. Cord blood troponin I levels were measured at delivery in both groups using a commercially available chemiluminescent immunoassay. Values ≤0.04 ng/mL were considered negative. Values >0.04 ng/mL were considered positive. The primary outcome was the presence of elevated troponin levels in both cases and controls as a surrogate marker for cardiac status. Our secondary outcomes included neonatal intensive care unit stay, low Apgar scores, neonatal acidosis, and hypoxia indicated by cord blood pH and base excess levels at the time of birth. Chi square and t tests were performed to compare social and obstetrical variables. A P value of <.05 was considered significant. A stratification by total bile acids range of <40 μmol/L, 40 to 100 μmol/L, and >100 μmol/L was performed to assess the relationship between the different severities of intrahepatic cholestasis of pregnancy (by risk of fetal demise with those with total bile acids of >100 μmol/L considered at greatest risk) and the likelihood of a positive troponin I result. Finally, a logistic regression analysis was performed to determine if levels of ≥10 μmol/L were associated with elevated troponin levels. RESULTS: The mean gestational age at delivery was 38.96±1.47 and 37.71±1.59 weeks of gestation in the controls and cases respectively (P<.001). The mean total bile acids values were 5.2±1.28 ng/mL and 43.2±40.62 ng/mL in the controls and cases respectively (P<.001). Cord blood troponin I was positive in 15 of 122 (12.30%) controls and in 20 of 87 (22.99%) cases. (P<.001). When further stratified by total bile acids levels of <40, 40 to 100, and >100 μmol/L, we found a positive correlation between higher total bile acids levels and a positive troponin I test (P=.002). When controlling for gestational age at delivery, maternal age, and body mass index, higher total bile acids levels were associated with a positive troponin I level (adjusted odds ratio, 1.015; 95% confidence interval, 1.004–1.026). CONCLUSION: Elevated troponin I was more likely to be found in patients with intrahepatic cholestasis of pregnancy than in those without intrahepatic cholestasis of pregnancy. When stratified by total bile acids levels, a positive troponin I level was more likely to be found with higher levels of total bile acids. In addition, as total bile acids levels increased, they were more likely to be associated with a positive troponin I level. Although there were no stillbirths in our cohort, our findings suggest a potential relationship between cardiac injury and high levels of total bile acids demonstrated by the presence of elevated troponin I levels in cord blood at the time of birth.